Profound differences between humans and rodents in the ability to concentrate salivary nitrate: Implications for translational research - Marcelo F Montenegro; Michaela L Sundqvist; Carina Nihlén; Michael Hezel; Mattias Carlström; Eddie Weitzberg; Jon O Lundberg (Redox Biology, 2016)
In humans dietary circulating nitrate accumulates rapidly in saliva through active transport in the salivary glands. By this mechanism resulting salivary nitrate concentrations are 10–20 times higher than in plasma. In the oral cavity nitrate is reduced by commensal bacteria to nitrite, which is subsequently swallowed and further metabolized to nitric oxide (NO) and other bioactive nitrogen oxides in blood and tissues. This entero-salivary circulation of nitrate is central in the various NO-like effects observed after ingestion of inorganic nitrate. The very same system has also been the focus of toxicologists studying potential carcinogenic effects of nitrite-dependent nitrosamine formation. Whether active transport of nitrate and accumulation in saliva occurs also in rodents is not entirely clear. Here we measured salivary and plasma levels of nitrate and nitrite in humans, rats and mice after administration of a standardized dose of nitrate. After oral (humans) or intraperitoneal (rodents) sodium nitrate administration (0.1 mmol/kg), plasma nitrate levels increased markedly reaching ~300 µM in all three species. In humans ingestion of nitrate was followed by a rapid increase in salivary nitrate to >6000 µM, ie 20 times higher than those found in plasma. In contrast, in rats and mice salivary nitrate concentrations never exceeded the levels in plasma. Nitrite levels in saliva and plasma followed a similar pattern, ie marked increases in humans but modest elevations in rodents. In mice there was also no accumulation of nitrate in the salivary glands as measured directly in whole glands obtained after acute administration of nitrate. This study suggests that in contrast to humans, rats and mice do not actively concentrate circulating nitrate in saliva. These apparent species differences should be taken into consideration when studying the nitrate-nitrite-nitric oxide pathway in rodents, when calculating doses, exploring physiological, therapeutic and toxicological effects and comparing with human data.